Towards the understanding of lubrication mechanisms in total knee replacements – Part I: Experimental investigations. (April 2021) - Nečas, David; Vrbka, Martin; Marian, Max; Rothammer, Benedict; Tremmel, Stephan; Wartzack, Sandro; Galandáková, Adéla; Gallo, Jiří; Wimmer, Markus A.; Křupka, Ivan; Hartl, Martin
Abstract: This contribution is aimed at the detailed understanding of lubrication mechanisms within total knee replacement. While Part I is focused on the experimental investigation, Part II deals with the development of a predictive numerical model. Here, a knee simulator was used for direct optical observation of the contacts between a metal femoral and a transparent polymer components. Transient dynamic conditions were applied. Mimicked synovial fluids with fluorescently labelled constituents were used as the test lubricants. The results showed that γ-globulin forms thin boundary lubricating film, being reinforced by the interaction of phospholipids and hyaluronic acid. Further development of lubricating film is attributed to albumin layering. Based on the results, a novel lubrication model of the knee implant is proposed. Graphical abstract: Image 1 Highlights: Employment of a knee simulator for exploration of lubrication mechanisms within TKA. Comparison of experimental results with predictive numerical model. Consideration of transient loading and kinematic conditions corresponding to ISO. Fluorescent labeling enabling to determine the role of specific fluid constituents. Novel lubrication model of TKA is proposed.